THE ROLE OF THE PROSECUTOR IN EFFORTS TO COMBAT CORRUPTION AS A CONTRIBUTION TO CRIMINAL LAW REFORM - Ria Sintha Devi; Alusianto (CV. RADJA PUBLIKA, 2024)
The objectives of this research are: 1). To find out the criminal act of corruption as a special crime. 2). To find out the supporting and inhibiting factors in handling the criminal act of corruption as a special crime. 3). To find out the efforts made to maximize the performance of handling the criminal act of corruption as a special crime. The results of this study are that efforts to eradicate corruption through fair law enforcement currently still seem to require a tough struggle. Because the crime of corruption is an extraordinary crime (extra ordinary crime) which is different from ordinary criminal crimes, the efforts that must be made require an integrated and extraordinary system. As an extraordinary crime (extra ordinary crime), eradicating corruption requires extraordinary political will so that the President as head of state becomes an important figure in mobilizing and coordinating the role of the Police, Prosecutors, Courts, and the Corruption Eradication Committee (KPK) to become a powerful force, so that KKN practices, such as bribery, price inflation, gratuities, and other abuses of authority carried out by civil servants or state officials, both at the central and regional levels, can have their room to move narrowed through extraordinary and integrated enforcement methods.